THE CONNECTION BETWEEN MENTAL HEALTH SYMPTOMS AND SOCIAL MEDIA EXPERIENCES IN ADOLESCENCE - ELLI TUOMISTO, RIITTAKERTTU KALTIALA, SARI FRÖJD, MAURI MARTTUNEN (Psychiatria Fennica)
ABSTRACT Objectives: Abundant use of social media is linked to young people's internalizing and externalizing mental symptoms. In this study, we examined how internalizing (depression) and externalizing (conduct symptom) symptoms are associated with whether social media produces positive or negative experiences in adolescents. Material and methods: The data was obtained from the Adolescent Mental Health Cohort and Replication study (AMHC) and collected during the academic years 2018–19. The study cohort consisted of 1386 voluntary 9th graders in Tampere, Finland. Depression was measured with R-BDI, conduct symptom with YSR and perceived social support with PSSS-R. Honesty of responding was assessed with a sincerity question, and socioeconomic adversities and age were controlled for. The data were analysed using cross-tabulations with chi-square statistics and logistic regression. Results: Girls reported more positive (79.1%) and negative (10.4%) social media experiences than boys (72.1% and 5.4%). Depression was inversely associated with positive and directly with negative social media experiences in both sexes. Conduct symptom was positively associated with both negative and positive social media experiences in girls but not in boys. Social support from friends and family attenuated the disadvantageous associations between mental health and social media experiences and was linked to more positive and fewer negative experiences. Inclusion of honesty and socioeconomic variables in the models did not alter these findings. Possible pathways between symptom dimensions and social media experiences are discussed. Future research should use longitudinal designs to establish causality.